2016
DOI: 10.1155/2016/8357025
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Efficacy of Laparoscopic Treatment for Colorectal Cancer in Patients with Schistosomiasis Japonica

Abstract: Introduction. Schistosomiasis is associated with numerous complications such as thrombocytopenia, liver cirrhosis, portal hypertension, and colitis. To the best of our knowledge, the feasibility and outcomes of laparoscopic colorectal surgery in patients with schistosomiasis have not yet been studied. Methods. In this study, the data of 280 patients with colorectal carcinoma along with schistosomiasis japonica infection who underwent laparoscopic or open colorectal surgery were retrospectively analyzed. Preope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Colorectal cancer is most likely to occur in the colon, rectum, and cecum. Radical surgery remains the main treatment for colorectal cancer[ 10 ]. However, studies have reported that 50% of patients might have local recurrence or metastasis within 2 years after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer is most likely to occur in the colon, rectum, and cecum. Radical surgery remains the main treatment for colorectal cancer[ 10 ]. However, studies have reported that 50% of patients might have local recurrence or metastasis within 2 years after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…From our previous studies, chronic schistosomiasis, similar to our patient, did not increase the risk of postoperative anastomotic bleeding in colorectal cancer. [ 20 ] Randi ML et al revealed that hemorrhage after surgical procedures was not uncommon in patients with ET. [ 21 ] Therefore, postoperative anastomotic bleeding is likely to be increased in patients with ET.…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in the treatment, the prognosis of CRC patients still is poor. The 5-year survival rate of CRC is approximately 50%, closely related to early diagnosis ( Yi et al, 2016 ; Zhang et al, 2018 ). Therefore, better understanding of the mechanisms of CRC carcinogenesis and metastasis is critical to identify novel biomarkers for early diagnosis and prognosis of CRC.…”
Section: Introductionmentioning
confidence: 99%